Pemikiran Filosofis Paulo Freire Tentang Kewarganegaraan dan Implikasinya Terhadap Pendidikan Kewarganegaraan: Paulo Freire's Philosophical Thoughts on Citizenship and Their Implications for Citizenship Education - Maulana, Daffa Fakhri; Wijaya, Dian Azizah Sadriansyah; Samsuri, Samsuri; Suyato, Suyato (Undiksha, 2025)
This study aims to describe Paulo Freire's profile and Paulo Freire's thoughts about citizenship and his involvement in citizenship education. This study uses a having to do with figuring out the quality of things without measuring them with numbers approach with library research, analysis of data that has been found, and drawing conclusions. This study uses an inductive approach. The first data source in this study comes from the book “Education of the Oppresed”. While secondary data sources come from books, scientific journals, as well as information from different other book-related sources to the object of research. Paulo Freire is a figure of humanist education. Although he never explicitly mentions civics and citizenship education in his works, Paulo Freire has left thoughts that have relevant contributions to civics and citizenship education. His thoughts on citizenship, which he calls the oppressed and the oppressors, are in line with the theory of critical citizenship. Freire has the thought of redefining the concept of citizenship for the oppressed so that they are free from the shadows of the oppressors and free both of them in a humane situation (humanization). In line with that his thoughts on education are also relevant to one of the schools of philosophy of citizenship education, namely critical citizenship education. The concept of education that Freire wants to build is education that liberates through education on dialogic issues.